PENANGANAN LIMBAH GERGAJIAN BATU ALAM PASCA ERUPSI MERAPI - Aji Pranoto; Saiful Huda (Universitas Sarjanawiyata Tamansiswa, 2015)
Stone sawing process in the area of Sleman leaves stone powder as waste, which discharged directly onto the ground can result into a barren land can not be planted and will also lead to ground can not absorb rainwater where this can lead to severe environmental damage, such as floods and droughts.To overcome this problem, the program is made of natural stone sawmill waste utilization through science and technology to the Community (IbM), with a program of making handicrafts using the main raw material waste sawdust and splinters of natural stone. The program is implemented with the main objective to empower people to be able to cope with waste and create new jobs. The resulting product consists ofCrafts (handcraft),Flower Pot and Mosaic The first is the handcraft produced with the main ingredient as the matrix is resin apoxy 95%, hardener 3%, plus 2% cobalt, as inforcement used stone dust particle with variable best comparison is 50% matrix, and 50% particle inforcment. whereas the mold to make handcraft materials using RTV silicone rubber 586 plus hardener. Both produced flowerpot with the main ingredient of cement and sawdust stone cast coupled with hardener (hardener), where the best compositions based on test results is 15% cement an d 75% stone dust. The molds used are made of Fiber Glass and steel molds. The resulting third is a mosaic, made of stone flakes aggregate prepared using cement and wire mesh material asÂ a binder and stone chips as forming ornaments. The mold using steel plate rectangular with size (20 x 20) cm. Of the three products produced, which has the best economic value is the Flower Pot, followed handcraft, while the mosaic has the lowest economic value